Improvement of Tryptophan Analysis by Liquid Chromatography-Single Quadrupole Mass Spectrometry Through the Evaluation of Multiple Parameters - la Cour, Rasmus; Jørgensen, Henning; Schjoerring, Jan K. (Frontiers in Chemistry, 2019)
Tryptophan is a key component in many biological processes and an essential amino acid in food and feed materials. Analysis of the tryptophan content in proteins or protein-containing matrices has always been a challenge. We show here that the preparation of samples prior to tryptophan analysis can be significantly simplified, and the time consumption reduced, by using ascorbic acid as antioxidant to eliminate the problem of tryptophan degradation during alkaline hydrolysis. Combined with separation by HPLC and detection by Single Quadrupole Mass Spectrometry, this allows the analytical run time to be reduced to 10 min. The alkaline hydrolysate obtained in the method presented here may be combined with the oxidized hydrolysate obtained when sulfur-containing amino acids are to be measured, thus essentially providing two analyses for the time of one.